Work Facility Design of the Ergonomic Tempeh Plastic Wraps Punching Tool Reduces Musculoskeletal Complaints and Working Time (A Case Study at MSME HM Tempe Murni, Ngoto, Yogyakarta) - Tri Budiyanto; Titan Restu Pambajeng (Jurnal Ilmiah Teknik Industri, 2022)
Abstract.   Tempe Murni small unit is a tempeh processing business located in Ngoto, Bangunharjo, Sewon, Bantul, Yogyakarta. There was a work process which caused muscle fatigue on the process of making holes on the tempeh wraps using manual tool because it had not met the ergonomic standard. The work posture of the workers in doing the work was sitting on the floor, the left leg was folded inward and the right leg was stretched forward a little bit, thus, it might cause musculoskeletal complaints. Therefore, it required an ergonomic tempeh plastic wrap punching tool which could reduce the musculoskeletal complaints and the working time of the workers.The research object was the workers in the process of making holes on the tempeh plastic wraps. This research used ergonomic and anthropometric approaches to determine the dimensions of the workers’ bodies. The Nordic Body Map (NBM) and the Visual Analogue Scale were used to determine the musculoskeletal complaints of workers.The results showed that the ergonomic design of the punching tool could reduce musculoskeletal complaints of pain sensation on the upper neck from the initial Visual Analog Scala (VAS) score of 65 into mild pain category with the scale score of 25. The initial back pain complaint with a moderate category with the scale score of 70 was reduced into mild pain category with the scale score of 16. The initial moderate pain on waist with the scale score of 70 was reduced into mild pain with the scale score of 18. The initial moderate pain on buttocks with the scale score of 70 was reduced into mild pain with the scale score of 26. The initial moderate pain on the lower part of the buttocks with a scale score of 69 was reduced into mild pain with a scale score of 29. The working time was reduced from 1.03 hours/unit into 0.52 hour/unit.